Determinant of Digital Payment Usage Intention on Tourism Destination - Yusuf, Abdul; Hidayat, Yosep Rahman; Kartika, Titing (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Digital payments make it easier for people to make transactions so that they are more effective and efficient. With the existence of digital payments, people's habits have changed in making payments, where the use of non-cash or cashless payments is more popular with people today. This research aims to examine and analyze the Influence of Ease of Use and Usefulness on Users' Interest in Digital Payment at tourism destinations. This study employs a quantitative method with a descriptive and verification approach. The population consists of visitors in 2024, determined using the Barchlay, Higgins, and Thompson formula, resulting in 100 respondents. The sampling method used is Incidental Sampling. This study utilizes scale range analysis and SEM-PLS analysis with tools including Smart PLS and Microsoft Excel. The findings reveal that there is no partial influence of ease of use on user interest in digital payments.